# Which of these are equivalent to each other? 9x-3x 12x-4 5x+x

Which of these are equivalent to each other? 9x-3x 12x-4 5x+x

## This Post Has 10 Comments

1. hjamileth77 says:

1. Brianna's thinking is incorrect because of course, when x is 0, the expression will equal whatever value isn't an x term. To find equivalent expression, you actually need to find which expressions have the same amount of x terms and the same value.

2. Expressions A and C are equivalent.

3. Expression A can be simplified, as you can do 9x - 3x = 6x, so your final expression would be 6x - 4. Expression C can also be simplified with 5x + x = 6x, which can then also be written as 6x - 4. This means both expressions have the same amount of x terms, and the same value, so they are equivalent.

I hope this helps!

2. Irdk1 says:

The two fractions equivalent to eachother are 2/3 and 6/9

Step-by-step explanation:

These fractions are equivalent because 6/9 can be reduced into 2/3. Also 6 is a multiple of 2 and 9 is a multiple of 3.

3. marvezunderwood says:

Expression A and C are correct because 9x - 3x = 6x and 5x + x = 6x, then -4

4. angelcamacho0219 says:

A and C are equivalent.

Step-by-step explanation:

When you simplify the expression, you find that only A and C simplify to make 6x-4

5. xelynncaldera says:

2/3 and 6/9

Step-by-step explanation:

you can just ÷ the fractions to turn them to decimals

2÷3=0.6666666667 and 6÷9=0.6666666667 they are the same so they are equivalent.

6. hhaacahh3588 says:

Briana's thinking is incorrect because the numbers are different when you substitute x with numbers other than 0.

the two equations that are equivalent to each other are,

5x+x−4 and 9x-3x-4

Step-by-step explanation:

Expression A: 9x−3x−4

​Expression B: 12x−4

​Expression C: 5x+x−4

First I will substitute x for each of the equations.

9x-3x-4

when x equals: , then y equals:

1                        =        9(1)-3(1)-4= 2

2                       =         9(2)-3(2)-4=8

3                       =      9(3)-3(3)-4= 14

Now for 12x-4

when x equals: , then y equals:

1                        =        12(1)-4=  8

2                    =         12(2)-4= 20

3                       =      12(3)-4=  32

And for the final equation:

5x+x−4

when x equals: , then y equals:

1                        =        5(1)+(1)−4= 2

2                       =         5(2)+(2)−4 = 8

3                       =      5(3)+(3)−4=14

Based on this you can now see that the two equations that are equal are:

5x+x−4 and 9x-3x-4

~CaityConcerto

7. c1100321311 says:

2/3 and 6/9

Step-by-step explanation

If the numbers are divisible by the corresponding denominator and numerators then the fractions will be equivalent.

8. straightbarz759 says:

Expressions A and C are equivalent.

Step-by-step explanation:

Expression A: 9x−3x−4   Combine like terms    6x -4

​Expression B: 12x−4   There are no terms to combine  12x-4

​Expression C: 5x+x−4  Combine like terms   6x -4

Brianna only looked at one particular value for x.  She must look at all values for x.

9. oscaryn7213 says:

9x-3x and  5x+x

Step-by-step explanation:

10. C4171 says:

9x-3x -4 simplified =6x -4
5x+x -4 simplified =6x -4

So, 9x-3x=6x-4